1986
DOI: 10.1152/ajpgi.1986.250.6.g842
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous prostaglandins in gastric alkaline response in the rat stomach after damage

Abstract: A role of endogenous prostaglandins in gastric alkaline response (an increase of luminal pH) and functional recovery was investigated in the rat stomach after damage with acidified taurocholate (TC, 20 mM) or aspirin (ASA, 40 mM). Exposure of the stomach to TC or ASA similarly produced a transmucosal potential difference (PD) reduction and enhancement of H+ backdiffusion. The PD was restored gradually with time, and this process was much faster in the case of TC compared with ASA. After exposure to TC, acid se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
46
0

Year Published

1987
1987
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 0 publications
3
46
0
Order By: Relevance
“…The involvement of endogenous PGs in the mucosal protection and the functional responses induced by mild irritants has been well-demonstrated by many investiga tors (11,(15)(16)(17). The increase of luminal pH in the stomach exposed to mild irritants is considered to be due to both inhibition of acid secretion and diffusion of HC03 (17), while the GMBF response may be mediated by endogenous PGs and capsaicin-sensitive sensory neu rons (11,18).…”
Section: Discussionmentioning
confidence: 99%
“…The involvement of endogenous PGs in the mucosal protection and the functional responses induced by mild irritants has been well-demonstrated by many investiga tors (11,(15)(16)(17). The increase of luminal pH in the stomach exposed to mild irritants is considered to be due to both inhibition of acid secretion and diffusion of HC03 (17), while the GMBF response may be mediated by endogenous PGs and capsaicin-sensitive sensory neu rons (11,18).…”
Section: Discussionmentioning
confidence: 99%
“…Prostaglandins are important compounds that are widely used in the pharmaceutical field because they inhibit platelet aggregation 9 , and have oxytocic 10 and gastric antisecretory actions 11 . G. vermiculophylla is a promising source of naturally occurring prostaglandins 4,12 .…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported that mild irritants produced both PD reduction and increase of pH of the rat stomach and suggested a causal relationship between these changes and adaptive cytoprotection induced by mild irritants (8)(9)(10). Thus, determination of gastric PD and pH may give some information about the involvement of adaptive cytopro tection in the mechanism of mucosal pro tection afforded by gastric secretagogues.…”
mentioning
confidence: 97%